The Multilateral Debt Relief Initiative : Progress Report on Implementation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
Reports on the implementation of the MDRI since December 2005, in line with the request made by Directors that a progress report be presented to the Board before the 2006 Spring Meetings. Includes a focus on the implementation of the initiative in the Fund, and covers implementation in other multilateral institutions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet